PENGARUH FINANCIAL DISTRESS, DEBT DEFAULT DAN UKURAN PERUSAHAAN TERHADAP OPINI AUDIT GOING CONCERN: (Studi Empiris pada Perusahaan Manufaktur Sektor Aneka Industri Subsektor Tekstil dan Garmen yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020) - Kharisma Putri Utami; Lodang Prananta Widya Sasana (Pusat Riset dan Inovasi Nasional, 2022)
This research aims to prove empirically the effect of financial distress, debt default, and firm size on going concern audit opinion. This research was conducted in various manufacturing companies in the textile and garment sub-sector. The research method used is quantitative associative. The type of data used is secondary data in the form of annual financial reports published on the Indonesia Stock Exchange (IDX) for 2016–2020. Samples were collected using purposive sampling method. The number of companies that were used as research samples were 14 companies with a research period of 5 (five) years, so that 70 observation data were obtained. The results of the F statistical test of financial distress, debt default, and company size simultaneously affect the going concern audit opinion. The results of the t-statistical test of the financial distress variable partially negatively affect the going concern audit opinion, while debt default partially has a positive effect on the going concern audit opinion, but the company size partially does not affect the going concern audit opinion.